2003
DOI: 10.1002/cplx.10063
|View full text |Cite
|
Sign up to set email alerts
|

Searching for complex CA rules with GAs

Abstract: An important problem in the theory of cellular automata (CA) is the research of complex rules

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In an earlier work [20], we used a genetic algorithm based on input-entropy, to find complex rules of class IV for 1D CA [4]. In the 2D case, with the increase of k ϭ ͉S͉ and of r, the exhaustive rule becomes nontreatable, and it is necessary to utilize a more simple form to be used as genome to start the evolutionary process.…”
Section: Formal Aspects Of Cellular Automatamentioning
confidence: 99%
“…In an earlier work [20], we used a genetic algorithm based on input-entropy, to find complex rules of class IV for 1D CA [4]. In the 2D case, with the increase of k ϭ ͉S͉ and of r, the exhaustive rule becomes nontreatable, and it is necessary to utilize a more simple form to be used as genome to start the evolutionary process.…”
Section: Formal Aspects Of Cellular Automatamentioning
confidence: 99%
“…Genetic algorithms have been used to address this problem by searching for particular behaviors in potentially complex rule spaces [10 -12]. The results of Bilotta et al [10] have shown that complex rule sets may actually have multiple values, which are the proportionality range of nondestructive rules. The behavior exhibited by multiple values explains the evolutive attractors as the cellular automata mature.…”
Section: Approachmentioning
confidence: 99%
“…This is one of the most important open questions in current Complexity Science [Bilotta et al, 2003a[Bilotta et al, , 2003b.…”
Section: Representing Parameter Spacementioning
confidence: 99%